Severe pre-eclampsia and infants of very low birth weight. - Szymonowicz, W (1987)
The effect of severe pre-eclampsia on the outcome of infants of very low birth weight was studied in a prospective case control study of 35 pairs of infants of comparable gestation. Significantly more infants were delivered before the onset of labour and by caesarean section in the group with pre-eclampsia. These babies tended to be smaller and had a higher incidence of hyaline membrane disease, patent ductus arteriosus, pulmonary air leak, and hypotension. They also required more intensive treatment with oxygen and mechanical ventilation. The significant difference in birth weight was still apparent at 2 years of age. Although the mean psychomotor developmental index and the incidence of specific neurodevelopmental impairments were not significantly different between the two groups, survivors in the group born to pre-eclamptic mothers had a significantly lower mean mental developmental index, and significantly more of these children had one or more impairments compared with the control group at 2 years of age.